A Novel Waterborne Coating Based On Styrene-Acrylic Copolymers For Construction Application - Mohamad Rashid, Nor Shafikah (Universiti Sains Malaysia, 2022)
This study consists of 3 stages which reflected by three objectives. At the first stage, this study investigated the effect of agitation speed, types of surfactants, feeding time monomers and concentration of monomers, initiator, and buffer to obtain seed nanoparticles (~70nm). At the second stage, the different compositions of two monomers; n-Butyl Acrylate (BA) and Styrene (Sty) was studied to obtain the high stability of polymer and were synthesized by seeded emulsion polymerization. At the third stage, the PBA-Sty films were casted on glass plate at room temperature for 24hours and the corresponding of glass transition temperature (Tg) on mechanical properties of poly (n-butyl acrylate-co-styrene) (PBA-Sty) films were studied using Differential Scanning Calorimetry (DSC) and tensile measurements. The chemical composition of materials was analyzed using Fourier Transform Infrared (FTIR). The pH, Total Solid Content (TSC), Dynamic Light Scattering (DLS), Zeta potential were studied in determining the characterization of seed nanoparticles and the stability of Seed-core emulsion. The Dynamic Light Scattering (DLS) showed S17 obtain the smallest particles size (66.53nm) by using non-ionic surfactant. The highest concentration of Styrene (Sty) (SC5) showed high polymer conversion, high glass transition temperature contributes to having high tensile strength of films by obtaining (48.06%), 24oC and (7.73Mpa) respectively this is due to the styrene provide the rigidity and high of hydrophobic chain which contribute to high Conversion of polymer. while highest concentration of Butyl Acrylate (BA) (SC1) showed high elongation at break (680.83%) which function in supplying the flexibility of film.